Unterrichten und Aneignen Eine pädagogische Rekonstruktion von Unterricht - Pollmanns, Marion (Verlag Barbara Budrich, 2019)
What is the relationship between the teaching of a teacher and the acquisition of the students, i.e. their handling of the "learning offer"? This is reconstructed in the interest of arriving at an empirically founded, pedagogical theory of teaching. The results of the objective-hermeneutic reconstruction are presented in presented in the form of four case studies for four lessons.The exploration of the ways in which adolescents acquire knowledge can be seen as an original contribution to reconstructive teaching research, since the side of "learning" not only traditionally remained underexposed in the pedagogical-didactical consideration of teaching, but also still does no attempt was made to develop them reconstructively. According to the leading thesis of the work, lessons can only be understood when the insights into the different ways of acquisition of the students are included, as they represent an interlacing of lessons and acquisition. Their relationship is worked out: This can be shown to what extent lessons can be but to what extent also as non-mediation.